The incidence and value of rectal examination in children with suspected appendicitis. - Dunning, P. G. (Royal College of Surgeons of England, 1991)
Rectal examination is considered an important part of the examination of patients presenting with abdominal pain. However, children find anal digitation unpleasant and it was our impression that doctors were becoming less insistent on performing a rectal examination. We performed an audit of rectal examination and assessed whether this made any difference to the management of children with acute abdominal pain. We looked at the records of 48 children from 1989 and 49 children from 1985 presenting with abdominal pain. We found that the rate of rectal examination was halved in this time. Diagnostic accuracy was similar in the two groups, and the morbidity rate was the same. These findings call into question the need for routine rectal examination in children with suspected appendicitis.